2022
DOI: 10.3389/fneur.2022.919312
|View full text |Cite
|
Sign up to set email alerts
|

Use of hand hydraulic dynamometers as an overall evaluation of the upper-limb weakness in patients with thoracic outlet syndrome

Abstract: Patients with neurogenic thoracic outlet syndrome report pain and upper-limb weakness. They complain about weakness occurring on the entire upper-limb, especially at the hand and the shoulder levels. Hydraulic dynamometers can reliably assess the strength of the hand, and isokinetic shoulder testing can provide accurate and reliable evaluations of the rotators strength. Yet, isokinetic proximal assessment needs expensive tools, whereas hydraulic hand dynamometers are cheap and easy to use. We aimed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Motor deficit is usually evaluated on examination with the MRC scale, but a more precise evaluation could be performed in this indication. Some recent data indicated that a systematic evaluation of strength with a grip and pinch gauge could reveal subclinical strength loss for patients with NTOS [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motor deficit is usually evaluated on examination with the MRC scale, but a more precise evaluation could be performed in this indication. Some recent data indicated that a systematic evaluation of strength with a grip and pinch gauge could reveal subclinical strength loss for patients with NTOS [ 50 ].…”
Section: Discussionmentioning
confidence: 99%